Understanding the Consumer Market in Improving the Buyer Behavior of Hong Kong Buns - Rodhiah, Rodhiah; Chandra, Dominikus Rinaldo; Nataputra, Rafael Pascal; Ray, Christian (CV. Proaksara Global Transeduka, 2024)
Every day, consumers are faced with numerous choices about what to purchase, and these choices are the main focus of marketing strategies. Major corporations invest heavily in researching consumer buying habits to gain insight into what, where, how much, and why consumers make purchases. While marketers can seek to understand consumer behavior, it is a challenging task. Oftentimes, consumers are unaware of the factors that drive their purchasing decisions. The partner or training site is a Hong Kong Buns culinary business located in Surabaya City. In its operations, it faces many obstacles, especially in terms of understanding consumer behavior in an effort to increase purchases. Meanwhile, this activity aims to help partner businesses understand these obstacles. The activity method is carried out by online training. Through this activity, it is hoped that the problems that arise in the company can be resolved, so as to increase sustainability in marketing the services sold accompanied by knowing more about the consumer market and buyer behavior. The output of this activity is in the form of publications to journals and IPR.